Kinetic Analysis on Cell Growth and Biosynthesis of Poly (3-Hydroxybutyrate) (PHB) in Cupriavidus Necator H16 - Khan, Maksudur R.; Reddy Prasad, D. M.; Hamidah, Abdullah; Mohidin Batcha, Abeed Fatima (International Academy Publishing (IAP), 2013)
Poly (3-hydroxybutyrate) (PHB) is a biodegradable polymer that can be synthesized through bacterial fermentation. In this study, Cupriavidus necator H16 was used to synthesize PHB by using jatropha oil as its sole carbon source. Experiments using 12.5 g/L of jatropha oil with the highest PHB accumulation of 8.6 g/L at 61.5hr was used to assess its kinetic pattern. Logistic and Leudeking-Piret model was used to evaluate the cell growth and PHB accumulation respectively and the theoretical values obtained corresponded well with the experimental data with slight deviation in cell growth and PHB accumulation at the end of stationary phase.